Antenatal depression and hematocrit levels as predictors of postpartum depression and anxiety symptoms. (30th April 2016) - Roomruangwong, Chutima; Kanchanatawan, Buranee; Sirivichayakul, Sunee; Maes, Michael
Abstract: The aim of this study is to delineate the risk factors of antenatal depression and its consequences, including postnatal depression, and to examine whether the hematocrit (Hct) is associated with maternal depression. The Edinburgh Postnatal Depression Scale (EPDS), Spielberger's State Anxiety Inventory (STAI), Kennerley and Gath Maternity Blues Assessment Scale (KGB), Beck Depression Inventory (BDI) and Hamilton Depression Rating Scale (HAMD) were assessed at the end of term (T1) and 2–3 days (T2) and 4–6 weeks (T3) after delivery in 126 women with and without antenatal depression. The Hct was measured at T1. Antenatal depression was significantly predicted by lifetime depression and premenstrual syndrome and less education. Antenatal depression was not associated with obstetric or neonatal outcomes. Antenatal depression symptoms strongly predict depression and anxiety symptoms at T2 and T3. The EPDS, KGB, STAI and BDI, but not the HAMD, scores, were significantly lower at T3 than before. The incidence of depression significantly decreased from T1 (23.8%) to T2 (7.8%) and T3 (5.3%). T1 Hct values significantly predicted the T3 postnatal EPDS, STAI, KGB and BDI scores. Delivery significantly improves depression and anxiety symptoms. Increased Hct in the third trimester is a biomarker of postpartum depression and anxiety symptoms. Highlights: Antenatal depression is predicted by a lifetime history of depression. Antenatal depressive symptoms strongly predict depressive and anxiety postpartum symptoms. The incidence of depression significantly decreases from the prenatal to the postpartum period. Delivery significantly improves depressive and anxiety symptoms. Prenatal hematocrit levels significantly predict postnatal depressive and anxiety symptoms.